Detection of Terahertz Frequencies in S-Doped GaSe Crystals Using Laser Pulses at Telecom Wavelengths - Olesya N. Shevchenko; Sergey L. Mikerin; Konstantin A. Kokh; Nazar A. Nikolaev (Applied Sciences, 2023)
Nonlinear optical crystals of gallium selenide are efficient up- and downconverters of infrared and terahertz frequencies. Their nonlinear properties have been investigated at wavelengths within the main transparency window. However, insufficient attention has been paid to studies at the telecommunication wavelength, especially for sulfur-doped crystals. Closing this gap, we report on the optical and electro-optical properties of GaSe(1–x)Sx crystals (where x = 0, 0.03, 0.12, 0.16, and 0.22). For this purpose, the refractive indexes of the ordinary waves at terahertz frequencies and at a wavelength of 1.55 μm have been measured. The detection efficiency of the subterahertz waves in the crystals was studied using Er-fiber laser pulses and compared with that of GaAs, the etalon electro-optical crystal, at this wavelength. This allows us to estimate the dependence of the electro-optic coefficient r22 of GaSe(1–x)Sx on the sulfur concentration. It was shown that the sample with x = 0.12 has the largest value of the electro-optical coefficient r22 = 1.26 pm/V and provides the highest detection efficiency among the samples. The potential of employing S-doped GaSe crystals as nonlinear optical converters for photonic devices operating at telecom wavelengths is discussed.